2008
DOI: 10.1038/cgt.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated gene transfer of interleukin-23 shows prophylactic but not therapeutic antitumor effects

Abstract: A novel cytokine interleukin (IL)-23 bears a structural and functional resemblance to IL-12. A recombinant adenovirus expressing IL-23N220L (recombinant replication-defective adenovirus (rAd)/IL-23N220L) that selectively secrets IL-23 was constructed and compared with rAd/IL-12N220L in terms of immunological and antitumor effects. In a prophylactic setting, vaccination with rAd/ ovalbumin (OVA) and rAd/IL-23N220L enhanced OVA-specific CD8 þ T-cell responses that were closely associated with complete protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is also necessary to note that while this manuscript was in preparation, a paper demonstrating a prophylactic, but not therapeutic, effect of adenovirally delivered IL-23 in variety of murine tumors was published25. This disparity in results may be due to the use of different murine tumor models, use of a mutant form of p4025 or initiating treatment at a different stage of the tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also necessary to note that while this manuscript was in preparation, a paper demonstrating a prophylactic, but not therapeutic, effect of adenovirally delivered IL-23 in variety of murine tumors was published25. This disparity in results may be due to the use of different murine tumor models, use of a mutant form of p4025 or initiating treatment at a different stage of the tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity in results may be due to the use of different murine tumor models, use of a mutant form of p4025 or initiating treatment at a different stage of the tumor model. In our studies, tumor bearing mice were treated on days 7, 9 and 11 starting with an average tumor size of 4mm compared to the studies performed in the previously mentioned paper, in which treatment was initiated when the average tumor volume reached 7mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The ELISPOT assay was performed as described before [35]. Briefly, splenocytes were co-incubated with E7 CD8 peptide (49-57) on an IFN-g capture Ab (BD Bioscience)-coated 96-well ELISPOT plate (Millipore).…”
Section: Elispot Assaymentioning
confidence: 99%
“…For example, mouse tumor cell lines expressing IL-23 can inhibit tumor growth in vivo (31); the use of adenovirus expressing IL-23 in established tumor models exhibited antitumor effects (32). It has also been reported that IL-23 can significantly enhance its antitumor effect only after adoptive transfer of peptide vaccine or antigen-specific T cells (33). The drawback of the aforementioned in vivo experiment is that it cannot accurately explain whether IL-23 acts directly on tumor cells and how to regulate its biological processes.…”
Section: Discussionmentioning
confidence: 99%